Marketing Communication Strategies Of Pt Hyundai Mobil Indonesia To Increase Electric Vehicle Purchase Intention In Jakarta - Dede Supriyatna; Zulaikha Zulaikha (Journal Research of Social Science, Economics, and Management, 2025)
The researcher analyzed the marketing of Hyundai electric cars in Jakarta. This is based on the fact that currently electric cars are experiencing significant growth and competitors from other brands that also produce and market electric vehicles have emerged, as well as what strategies Hyundai Indonesia uses to attract consumer interest. This study aims to identify and analyze good and effective marketing communication strategies to increase Hyundai electric car sales in Jakarta. Marketing communication strategy is a communication activity that is compiled by a company or organization to convey messages about products, services, or brands to the intended market segment, this is expected to influence consumer attitudes and purchasing behaviors. The method used was to conduct a descriptive qualitative approach with interviews with employees of the Hyundai Cilandak Branch. Data collection was carried out through case studies by conducting interviews. The results of the analysis show that integrated and systematic marketing communication including the use of digital media, social interaction, campaigns, education talk and the use of brand image are able to increase brand awareness and consumer buying interest in Hyundai electric cars. This strategy can not only increase product sales in big cities like Jakarta, but can also support development broader smart mobility ecosystem in Indonesia. These results are expected to provide recommendations for Hyundai Indonesia to strengthen its position in increasing electric vehicle sales in the Jakarta market, as well as contribute to the development more effective marketing strategy the automotive industry that produces electric cars in Indonesia.